The Role of Legal Aid And Consultation Agencies Faculty of Law University of Muhammadiyah Sukabumi to Prevent Domestic Violence - Kusumah, Haidan Angga Kusumah; Ginalita Dwi Putri2, R Eriska; Rachmawati, Ike (Faculty of Law, Universitas Lampung, 2023)
This research was motivated by the ineffectiveness of the efforts of the government and social institutions, law enforcement agencies in reducing the number of domestic violence that occurs in the community, and especially for the role of legal aid institutions that provide legal assistance in assisting domestic violence cases is still ineffective, because people who need legal assistance in accessing legal aid in domestic violence cases are still low, especially people in the Sukabumi Regency area in terms of prevention and Legal assistance in domestic violence cases by Legal Aid Providers is still not well coordinated. Therefore, research was conducted with concrete objectives on how to step the strategy pattern of the role of the Legal Assistance and Consultation Institute (LBKH) Faculty of Law, University of Muhammadiyah Sukabumi, in tackling domestic violence crimes in Sukabumi. The research method used is descriptive-analytic, that is, explaining existing data from relevant materials and analyzing them with reference to juridical foundations. The wrong approach that will be taken is to make observations in advance of an existing problem by being studied qualitatively and quantitatively, making a pattern the concept of handling the provision of legal assistance between LBKH and the Local Village Area. The results showed that with a pattern of strategic concepts applied between the cooperation of LBKH and the local village government, it can be possible to emphasize domestic violence cases in Sukabumi Regency by also focusing on the concept of domestic violence together with social institutions, law enforcement, and other institutions. With legal aid institutions in the regions tackling domestic violence cases in the community, solutions can be found by forming a pattern of joint handling concepts both in terms of prevention and legal assistance can run effectively, especially so that the role of legal aid institutions in providing legal assistance for domestic violence cases is maximized, especially in terms of prevention and legal assistance.